Literature Review: The Influence of Forensic Accounting, Independence, and Audit Experience on Fraud Detection - Kuntadi, Cris; Septiani, Anggi Kirana; Adawiyah, Rofiana (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research Aim : This article reviews research on the factors that influence fraud detection, there is Forensic Accounting, Independence, and Audit Experience. The purpose of this literature review is to develop hypotheses about the influence between variables for use in future research. Design/Method/Approach : The method of writing this scientific article is a qualitative method and literature review (literature review). Researching theories and relationships or influences between variables from books and online journals sourced from Mendeley, Google Scholar, and other online media sources. Research Finding : The results of this literature review show the influence of forensic accounting variables, independence, and audit experience, on fraud detection. This means that the better forensic accounting knowledge, independence, and audit experience you have, the better the implementation of fraud detection will be. Theoretical contribution/Originality : - Research limitation : -